Performance Optimization for PbTe-Based Thermoelectric Materials - Hao, Xinxing; Chen, Xinqi; Zhou, Xing; Zhang, Lin; Tao, Junhui; Wang, Chuanhui; Wu, Tian; Dai, Wei (Frontiers in Energy Research, 2021)
Thermoelectric material is a kind of functional material that uses the movement of carriers inside a solid to realize the direct mutual conversion of heat and electric energy. It provides a safe, reliable, pollution-free, noise-free, all-solid-state power generation and cooling method and has a wide range of application prospects. Among them, the characteristics of low valence band degeneracy, low effective quality of conduction band, strong phonon non-harmonicity, simple crystal structure and adjustable microstructure have made PbTe-based materials the focus of research in the thermoelectric field. In this review, two latest strategies to improve the thermoelectric properties of PbTe-based materials are discussed, and the challenges for the further development of PbTe-based thermoelectric materials and the prospects for the future are also outlined.